The Chalice of the Gods - Riordan, Rick; Khatib, Khadijah (London puffin books, 2024)
Percy Jackson has saved the world multiple times - battling monsters, Titans, even giants - but these days the modern-day son of Poseidon is hoping for a regular final year at school. Too bad the Greek gods have other plans, and three new quests for Percy to complete. First up: the cupbearer of the gods, Ganymede, is missing his golden chalice. Not only is this embarrassing (why do the gods keep losing their magical items?), it's also potentially disastrous. One sip from the cup will turn any mortal into a powerful god. And the old gods do not take kindly to newbies. Can Percy and his friends Annabeth and Grover find the chalice before it falls into the wrong hands? And even if they do, will they be able to resist its awesome power. . .? Readers new to the Percy Jackson universe and long-time fans will love this epic adventure - full of legendary heroes, mythical creatures, ancient Greek gods and enduring friendship - from the global bestseller Rick Riordan
English stories
Keywords: Action & Adventure; Fantasy & Magic; Juvenile Fiction; Monsters